A ZnO nanowire bio-hybrid solar cell. (28th December 2016) - Yaghoubi, Houman; Schaefer, Michael; Yaghoubi, Shayan; Jun, Daniel; Schlaf, Rudy; Beatty, J Thomas; Takshi, Arash
Abstract: Harvesting solar energy as a carbon free source can be a promising solution to the energy crisis and environmental pollution. Biophotovoltaics seek to mimic photosynthesis to harvest solar energy and to take advantage of the low material costs, negative carbon footprint, and material abundance. In the current study, we report on a combination of zinc oxide (ZnO) nanowires with monolayers of photosynthetic reaction centers which are self-assembled, via a cytochrome c linker, as photoactive electrode. In a three-probe biophotovoltaics cell, a photocurrent density of 5.5 μ A cm −2 and photovoltage of 36 mV was achieved, using methyl viologen as a redox mediator in the electrolyte. Using ferrocene as a redox mediator a transient photocurrent density of 8.0 μ A cm −2 was obtained, which stabilized at 6.4 μ A cm −2 after 20 s. In-depth electronic structure characterization using photoemission spectroscopy in conjunction with electrochemical analysis suggests that the fabricated photoactive electrode can provide a proper electronic path for electron transport all the way from the conduction band of the ZnO nanowires, through the protein linker to the RC, and ultimately via redox mediator to the counter electrode.